2016
DOI: 10.1016/s0140-6736(15)00056-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure prophylaxis to prevent the acquisition of HIV-1 infection (PROUD): effectiveness results from the pilot phase of a pragmatic open-label randomised trial

Abstract: SummaryBackgroundRandomised placebo-controlled trials have shown that daily oral pre-exposure prophylaxis (PrEP) with tenofovir–emtricitabine reduces the risk of HIV infection. However, this benefit could be counteracted by risk compensation in users of PrEP. We did the PROUD study to assess this effect.MethodsPROUD is an open-label randomised trial done at 13 sexual health clinics in England. We enrolled HIV-negative gay and other men who have sex with men who had had anal intercourse without a condom in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
1,403
9
39

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,616 publications
(1,483 citation statements)
references
References 21 publications
32
1,403
9
39
Order By: Relevance
“…Worldwide a number of research studies in different populations have shown that consistent use of HIV-PrEP can be an efficacious and effective prevention intervention. Two European studies of oral PrEP using a combination of tenofovir and emtricitabine coformulated as Truvada (t) among men who have sex with men (PROUD trial [12] in the UK and the IPERGAY trial [13] in France) have reported during 2015. Both trials demonstrated a reduction in HIV acquisition of 86% in intent to treat analyses.…”
Section: Hiv Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide a number of research studies in different populations have shown that consistent use of HIV-PrEP can be an efficacious and effective prevention intervention. Two European studies of oral PrEP using a combination of tenofovir and emtricitabine coformulated as Truvada (t) among men who have sex with men (PROUD trial [12] in the UK and the IPERGAY trial [13] in France) have reported during 2015. Both trials demonstrated a reduction in HIV acquisition of 86% in intent to treat analyses.…”
Section: Hiv Preventionmentioning
confidence: 99%
“…The evidence for efficacy and effectiveness of antiretroviral agents to reduce onward transmission from people who are HIV positive [14,16] as well as prevent HIV acquisition in those who are HIV free (HIV -Pre Exposure Prophylaxis HIV -PrEP) [12,13] continues to expand, making important additions to the prevention toolkit.…”
mentioning
confidence: 99%
“…90% of all adults receiving ART were virally suppressed' (Yin, et al 2014, 5). In addition to treatment as prevention (TasP) significantly inhibiting the transmission of HIV (WHO 2015), prevention of infection is also made possible through post-exposure prophylaxis and the ongoing development (and availability) of PrEP (pre-exposure prophylaxis) -which brings with it the joint, yet contradictory, possibilities of control and protection alongside (HIV related) concerns of side effects and managing adherence and stigma (Liu et al 2014;Young et al 2014;McCormack et al 2015). These technical developments in HIV intervention generate their own complexities, requiring an acute and dynamic understanding of the relationships among HIV, medical technologies and the body (Rosengarten 2009).…”
Section: Biotechnical Possibilitiesmentioning
confidence: 99%
“…The success of ART has reframed the lived experience of HIV undoubtedly but not entirely in the manner suggested by UNAIDS (2014) or indeed, Barack Obama in his most recent reference to the 'achievement of an AIDS-free generation' (PEPFAR 28 July 2015). The reasons for this are many and varied and highlight the social, economic and cultural limitations and shortcomings of clinical intervention and technologies (Hunter 2015;Johnson et al 2015). Nowhere is this more evident than in the experience of HIV and AIDS-related stigma.…”
Section: Biotechnical Possibilitiesmentioning
confidence: 99%
See 1 more Smart Citation